Molecular Cloning of Heat Shock Protein 60 (SpHSP60) from Schizothorax prenanti and the Gene Expressions of Four SpHSPs during Lipopolysaccharide (LPS) Infection - Jianlu Zhang; Jiqin Huang; Cheng Fang; Wanchun Li; Hu Zhao; Fei Kong; Han Zhang; Hongxing Zhang; Qijun Wang (Fishes, 2022)
Heat shock proteins (HSPs) play a key role in anti-stress and immune processes and are associated with autoimmune diseases. In order to explore the immunological role of HSPs from Schizothorax prenanti (S. prenanti), SpHSP60 was cloned for the first time in this study, and the gene expressions of SpHSP27, SpHSP60, SpHSP70 and SpHSP90 in the hepatopancreas, head kidney, hindgut and spleen were analyzed by quantitative real-time PCR (qPCR) after treatment with lipopolysaccharide (LPS). The open reading frame of the SpHSP60 gene (GenBank accession number ON245159) is 1728 bp. It encodes a protein of 575 amino acids. Its C-terminus is a highly conserved and repeated glycine sequence, which is an important cofactor in ATP binding. Compared with the control group, most of the SpHSPs were significantly upregulated in the tissues examined at 12 or 24 h after LPS challenge. The most abundant expression of SpHSP70 was found in the head kidney at 24 h after LPS injection, followed by SpHSP27 in the spleen at 24 h; both of these SpHSPs displayed strong expression under the LPS stresses, about 20–70 fold more than that of SpHSP60 and SpHSP90. The temporal expression patterns of the four SpHSP genes were different in the four tissues examined. Taken together, the results suggest that SpHSP27, SpHSP60, SpHSP70 and SpHSP90 participate in innate immunity stimulated by LPS, and the response intensity of the SpHSPs was organ-specific, indicating they could provide early warning information against bacterial infection. The findings in our study will contribute to better understanding the biological processes and important roles of SpHSPs involved in defending against pathogenic bacterial challenge.